‘Chitta’, “The Mind-stuff” as a Cognitive Apparatus: Model of mind and process of cognition as in Yogasutra of Patanjali - Upadhyay-Dhungel, K; Dahal, BK (Janaki Medical College Journal of Medical Science, 2014)
Background and Objectives: Medical sciences have developed tremendously but yet it has to understand the brain, mind, consciousness and cognition process. In this article, authors have made an attempt to present a process of cognition with a model of mind explained in yoga sutra of Patanjali. Material and Methods: Understanding the mind with the modern scientific tools is often difficult. Here an attempt has been made to understand mind with the help of various literature in yoga especially in yoga sutra of patanjali, a valid text of yoga. Hermeneutical approach, a method used in qualitative method of inquiry is used for this study. Reading, re-reading the texts and finding the meaning out of the text is the process used. Results: A model of mind has been proposed as finding of the study. This model of mind has a ‘chitta’ (Mind stuff) as a cognitive apparatus and important component for cognition. ‘Chitta’ interacts with the external manifested world (Prakriti). ‘Chitta’ has Mana, Buddhi and Ego as Antakahrana (internal organ) and ‘Indriyas’ (Five Gyanendriyas and Five Karmaindriyas) as external organ. This concept of mind and cognition works for the plane of ‘chitta-vritti’ state where vrittis are the external world. But YSP also talks about next plane of cognition which is beyond the scope of this study. Conclusion: A cognitive model explaining the concept of mind forms a major finding of this research. This finding may initiate future researches in the field of understanding the mental processing and acts as links between ancient wisdom of yoga and modern concept on mind and cognition and how they can complement each other. This model of concept of mind can also be used as concept for psychological counseling and psychological therapy. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11390 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1): 10-16